LEGAL BASIC OF BCG-THERAPY FOR BLADDER CANCER IN MUNICIPAL POLYCLINICS - M. M. Zorina (Tuberkulez i Bolezni Lëgkih, 2016)
The article presents brief data from the literature about the history of BCG vaccine development (Bacille bilie' Calmette-Gue'rin), results of meta-analyses aimed at the evaluation of BCG-therapy efficiency in Ta-T1 bladder cancer. Below one can read descriptions of clinical cases when side effects and complications of this method developed according to the literature data and results of authors' personal observations. The main reason of low level of BCG-therapy use in Russia is low awareness of medical workers about the legal grounds for application of this method. The article gives the list of acting legal acts regulating provision of epidemiological safety when applying BCG-therapy and describes the technique for using this method in municipal polyclinics in compliance with the above legal acts.